A checklist of the barnacles (Crustacea: Cirripedia: Thoracica) of the Persian Gulf and Gulf of Oman with nine new records - Shahdadi, Adnan; Sari, Alireza; Naderloo, Reza (Zootaxa, 2014)
The present annotated checklist contains 43 species of thoracican barnacles known to date from the area, 33 and 26 from the Persian Gulf and the Gulf of Oman, respectively. Nine species are new records for the area including Amphibalunus subalbidus (Henry, 1973), Armatobalanus allium (Darwin, 1854), Chelonibia patula (Ranzani, 1818), Conchoderma hunteri (Owen, 1830), Lepas anserifera Linnaeus, 1767, Lithotrya valentiana Reinhardt, 1850, Megabalanus coccopoma (Darwin, 1854), Megabalanus occator (Darwin, 1854) and Platylepas hexastylos (Fabricius, 1798), of which A. subalbidus and M. coccopoma are reported as alien species from the region.